Measurement of the new anticoagulants - Harenberg, Job; Krämer, Roland (Thrombosis research, 2012)
New oral anticoagulants are given at fixed daily doses without laboratory dose adjustment for prevention of venous thromboembolism following elective total knee- and hip replacement, for treatment and prevention of recurrent events of acute venous thromboembolism, and for prevention of embolic events in atrial fibrillation. However, it may be necessary to determine the anticoagulant effect of new oral anticoagulants in special patient populations such as in elderly, for renal impairment, before operation, bleeding or thrombotic episodes and to monitor self-compliance. Oral factor Xa and oral thrombin inhibitors influence dose dependently global and specific coagulation assays. Standardization of assays is currently undertaken. Determination of the new oral anticoagulants in serum samples would facilitate blood sampling and analysis from samples taken and stored for creatinine or other biochemical parameters. Point of care methods from plasma or urine for the new oral anticoagulants would improve patient care. First data demonstrate the feasibility of such assays in urine.
Gesehen am 12.07.2018